Relationship between Basic Psychological Needs and Problematic Internet Use of Adolescents: The Mediating Role of Life Satisfaction - Okur, Sinan; Özekes, Mustafa (Addicta: The Turkish Journal on Addictions, 2021)
This study aimed to examine the mediating role of life satisfaction in the relationship between basic psychological needs of adolescents and problematic internet use. The model established on this mediating role was tested using the self-determination theory. The sample of the study included 1318 adolescents, of whom 796 were female and 522 were male students. The age range of the individuals participating in the study varied between 14 and 17 years, and the average age was 15.38 (Standard Deviation= 4.77). The study obtained data through the Problematic Internet Use Scale-Adolescent Form, Psychological Needs Scale-High School Form, Life Satisfaction Scale, and Personal Information Form. The data were analyzed using conditional process analysis. The results revealed that basic psychological needs significantly negatively predicted problematic internet use (r2=0.15; p ≤ 0.01) and positively predicted life satisfaction (r2=0.28; p ≤ 0.01); whereas life satisfaction significantly negatively predicted problematic internet use (r2=0.08; p ≤ 0.01). Using the Self-determination Theory, the study determined that life satisfaction has a partial mediating role in the relationship between basic psychological needs and problematic internet use among high school students (c′=0.06; p ≤ 0.01). The study findings confirmed the established model. The obtained results are discussed and interpreted against relevant literature. Some suggestions have been offered to families, school counselors, and researchers.
Keywords: Internet; life satisfaction; problematic internet use; psychological needs